2016
DOI: 10.1177/0020872814562481
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between exposure to interparental violence and child physical abuse in childhood and the impacts on mental health problems in later young adulthood among South Korean college students

Abstract: Family violence including interparental violence and child maltreatment is a pervasive social problem that affects all societies worldwide, and its detrimental impacts on people’s mental health are well documented. However, studies on family violence in South Korea are still limited. By utilizing an exploratory retrospective research design, this study explored the extent of childhood experience of family violence and the long-term impacts on mental health outcomes. A total of 90 college students in South Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
2
8
1
Order By: Relevance
“…However, dual harm and any single type of maltreatment had no differences in internalizing problems. This result was similar to Han et al's (2016) outcomes, which found that South Korean college students who were exposed to a single form of violence showed equally high levels of internalizing problems as those exposed to dual harm.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, dual harm and any single type of maltreatment had no differences in internalizing problems. This result was similar to Han et al's (2016) outcomes, which found that South Korean college students who were exposed to a single form of violence showed equally high levels of internalizing problems as those exposed to dual harm.…”
Section: Discussionsupporting
confidence: 80%
“…In Taiwan, those experiencing multi-type family maltreatment demonstrated more internalizing and externalizing problems than those experiencing only one type of maltreatment (Shen, 2009). However, among South Korean young adults, exposure to a single type of maltreatment resulted in equally high levels of internalizing and externalizing problems as those who experienced dual family harm (Han, Choi, & Jung 2016).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although ample evidence supports the enduring relationships between different forms of childhood adversities with negative mental health outcomes in East Asia [12,37,38], a significant gap remains in understanding how different ACE patterns may associate with different mental health risk profiles in this cultural group. Addressing this knowledge gap would have significant implications for the design and implementation of targeted and culturally appropriate prevention and intervention programs.…”
Section: Aces Pattern and Mental Health In Young Adulthoodmentioning
confidence: 99%
“…Even though this scale has not been used with college students in Hong Kong, the original ABCL scale has been widely used in cross-cultural studies (Chan et al, 2003). Also, a study with college students in South Korea that used the exact same 28 items showed a very good reliability (α = .89) (Han et al, 2015). The scale in this study also shows a very good reliability (α = .89).…”
Section: Methodsmentioning
confidence: 99%